An Ineffective Institutional Investors Law in Indonesia? Why Bother - Lie, Luther; Dewi, Yetty Komalasari (UI Scholars Hub, 2021)
Corporate governance failures are one of the major factors that have crippled the Indonesian economy through financial crises. In response, the OECD has prescribed Principles II and III of the G20/OECD Principles of Corporate Governance to ensure the rights and equitable treatment of all shareholders and the acknowledged role of institutional investors in improving corporate governance. Institutional investors play a significant role as corporate monitors in protecting the public investors’ money and improving corporate financial performance. They are therefore acknowledged as the policies of economic crises, creators of firm values, and drivers of economic development. However, as this paper explains, the existing legal framework of institutional investors in Indonesia is implicit and inadequate to comply with these Principles. It draws hard lessons from, for example, the Malaysian legal framework of institutional investors, which are advanced but flawed, paving for the exceptional 1MDB multibillion dollars of corruption and political mayhems. Stakeholder governance on institutional investors that leaves to private ordering and makes government intervention unnecessary is counterproductive to protect the interests of stakeholders. This paper proposes the rules of the game for institutional investors in Indonesia that could maintain their nimbleness to drive corporate financial performance and economic development.